HEALTH EXAMINATION OF CONGREGATIONS OF MAJELIS TAKLIM ATHOYYIBAH KEMUNING (ATHOYYIBAH KEMUNING ISLAMIC LEARNING INSTITUTION) SOUTH JAKARTA - Suralaga, Cholisah; Syamsiah, Siti; Tsabita, Taqiyya Hasya (International Journal of Engagement and Empowerment (IJE2), 2024)
The Athoyyibah Islamic Learning Institution, commonly known as Majelis Taklim Athoyyibah, attracts a consistent crowd of congregations. Approximately 70 individuals gather at Majelis Taklim every Wednesday for Quranic recitation, Tajwid study sessions, and religious lectures. Most attendees are housewives, while some are employed but attend occasionally due to the weekday scheduling of the sessions. The members of Majelis Taklim span a wide age range, typically between 30 and 70 years old. Many attendees also contend with health issues such as hypertension, diabetes mellitus, and joint pain. To conduct health examinations for the mothers of Majelis Taklim Athoyyibah Kemuning, South Jakarta, to detect disease symptoms early. Data was collected from 40 Majelis Taklim Athoyyibah Kemuning members during the health examination. Most participants (47.5%) were between 51-60 years old. Among them, eight individuals (20%) were found to have prehypertension, while 13 individuals (32.5%) were diagnosed with hypertension. Additionally, 15 participants (37.5%) reported symptoms of gastritis, and 50% of the congregants experienced joint pain. The health examination revealed a high prevalence of prehypertension, hypertension, gastritis, and joint pain among the members of Majelis Taklim Athoyyibah Kemuning. It is recommended that these individuals undergo regular health check-ups conducted by healthcare professionals or at health service centers to facilitate early detection of illnesses. Furthermore, those diagnosed with diseases should adhere to prescribed treatment regimens and adopt healthy lifestyle practices to manage their conditions effectively